Prevalence of self-reported comorbidities in HIV positive and HIV negative men who have sex with men over 55 years-The Australian Positive & Peers Longevity Evaluation Study (APPLES). - Kathy Petoumenos; Robin Huang; Jennifer Hoy; Mark Bloch; David J Templeton; David Baker; Michelle Giles; Matthew G Law; David A Cooper (PLoS ONE)
In Australia, almost half of HIV-positive people are now aged over 50 and are predominately gay and bisexual men (GBM). Compared to the general HIV-negative population, GBM engage more in behaviours that may increase the risk of age-related comorbidities, including smoking, high alcohol consumption and recreational drug use. The objective of APPLES was to compare comorbidities and risk factors in HIV-positive older GBM with an appropriate control group of HIV-negative GBM. We undertook a prospectively recruited cross-sectional sample of HIV-positive and HIV-negative GBM ≥ 55 years. Detailed data collection included clinic data, a health and lifestyle survey, and blood sample collection. We report key demographic, laboratory markers and self-reported comorbidities by HIV status. For selected comorbidities we also adjust HIV status a priori for age, smoking and body mass index. Over 16 months 228 HIV-positive and 218 HIV-negative men were recruited. Median age was 63 years (IQR: 59-67). Although more HIV-positive men reported having ever smoked, smoking status was not statistically different between HIV positive and HIV negative men (p = 0.081). Greater alcohol use was reported by HIV-negative men (p = 0.002), and recreational drug use reported more often by HIV-positive men (p<0.001). After adjustment, HIV-positive men had significantly increased odds of diabetes (adjusted Odds ratio (aOR): 1.97, p = 0.038), thrombosis (aOR: 3.08, p = 0.007), neuropathy (aOR: 34.6, P<0.001), and non-significantly increased odds for heart-disease (aOR: 1.71, p = 0.077). In conclusion, HIV-positive GBM have significantly increased odds for key self-reported comorbidities. This study underscores the importance of an appropriate HIV-negative control group for more accurate evaluation of the risk and attribution of age-related comorbidities in HIV-positive people.